Maternal N‐acetyl‐cysteine prevents neonatal brain injury associated with necrotizing enterocolitis in a rat model. (12th January 2021) - Zmora, Osnat; Gutzeit, Ola; Segal, Linoy; Boulos, Sari; Millo, Zvika; Ginsberg, Yuval; Khatib, Nizar; Fainaru, Ofer; Ross, Michael G.; Weiner, Zeev; Beloosesky, Ron
Abstract: Introduction: Preterm infants with necrotizing enterocolitis (NEC) are at increased risk of cerebral injury and neurodevelopmental dysfunction. N‐acetyl‐cysteine (NAC) is a known anti‐inflammatory and antioxidant agent. Currently, there is no prophylactic treatment in clinical use to prevent NEC and its neurodevelopmental sequelae. We sought to determine whether brain inflammation/apoptosis accompanies NEC systemic inflammation, and whether it can be attenuated by maternal NAC treatment during pregnancy and/or in the neonatal period in a rat model. Material and methods: An established NEC newborn model (hypoxia 5% O2 for 10 min and formula feeding thrice daily, beginning on day 1 for 4 days) was used in Sprague‐Dawley rat pups (n = 32). An additional group of pups (n = 33) received NAC (300 mg/kg intraperitoneal thrice daily) in addition to NEC conditions (NEC‐NAC). Control pups (n = 33) were nursed and remained with the dam in room air. Two additional groups included pups of dams treated once daily with NAC (300 mg/kg intravenous) in the last 3 days of pregnancy. After birth, pups were randomized into NAC‐NEC (n = 33) with NEC conditions and NAC‐NEC‐NAC (n = 36) with additional postnatal NAC treatment. Pups were sacrificed on the fifth day of life. Pup serum interleukin (IL)‐6 protein levels, and brain nuclear factor kappa B (NF‐κB) p65, neuronal nitric oxide synthase (nNOS), Caspase 3, tumor necrosis factor alpha (TNF‐α), IL‐6 and IL‐1β protein levels were determined by ELISA, western blot and TUNEL staining, and the groups were compared using analysis of variance (ANOVA). Results: NEC pups had significantly increased serum IL‐6 levels compared with the control group as well as increased neuronal apoptosis and brain protein levels of NF‐κB, nNOS, Caspase 3, TNF‐α, IL‐6 and IL‐1β compared with control. In all NAC treatment groups, levels of serum IL‐6, neuronal apoptosis and brain NF‐κB, nNOS, Caspase 3, TNF‐α, IL‐6 and IL‐1β protein levels were significantly reduced compared with the NEC group. The most pronounced decrease was demonstrated within the NAC‐NEC‐NAC group. Conclusions: NAC treatment can attenuate newborn inflammatory response syndrome and decrease offspring brain neuroapoptosis and inflammation in a rat model of NEC by inhibition of NF‐κB, nNOS and Caspase 3 pathways.